Riesgos físicos, ergonómicos y mecánicos en las actividades de los trabajadores de la planta envasadora Duragas Bellavista - Zambrano Zambrano, Jorge Luis (2024)
It is essential that Gas (LPG) bottlers establish rigorous safety policies and procedures to avoid workplace accidents. This research aimed to evaluate the physical, ergonomic and mechanical risks at the Duragas Bellavista gas bottling plant. Three phases were carried out, which included a diagnosis of occupational safety in the company, the identification and evaluation of physical, ergonomic and mechanical risks, as well as compliance with current regulations, culminating with the proposal of preventive measures to address the identified risks. In the first phase, it was observed that employees showed a high level of compliance with safety measures, especially regarding signage and the use of personal protective equipment. However, significant areas of improvement were identified in worker training and awareness. The second phase revealed that the company is made up of three areas (administrative, production and warehouse) in which 43 employees work. These workers are exposed to various risks, such as lack of ventilation, excessive noise levels, inadequate postures, repetitive movements, entrapments, falling objects, among others. Appropriate preventive measures were proposed to address these risks, being shared and discussed with the company's workers and managers for their implementation. Ultimately, this research showed that the activities carried out by workers have a significant impact on the identified risks.